Study of Alloy Springs with Magnetorheological Dampers for Vibration Isolator Device - Chen, Dyi-Cheng (Proceedings of Engineering and Technology Innovation, 2017)
Vibration is a factor that must be controlled during the manufacturing process; variation in workpiece dimensions often results in inaccuracies due to vibration. This study adopted a spring and electromagnetic-repulsion and magnetorheological damper that can absorb the energy of external vibrations and deduced the influential vibration factors. ANSYS was employed to determine the energy that could be absorbed by the vibration isolation device under machine vibration, and the Taguchi method of quality engineering was used to design the structure of the device (metal spring, wire diameter, and material). The usability of the product was examined for application in computer numerical control and traditional machines. The considered parameters of the magnetorheological fluid were density, the coefficient of elasticity, and Poisson’s ratio. The results indicated that spring wire diameter exerted the strongest effect on the device’s performance and that the electrical current provided to the damper could be buffered.